Customer Satisfaction on Service Quality of Real Estate Agencies: An Empirical Analysis with reference to Kochi Corporation Area of Kerala State in India - Nasar K. K.AND Dr. Manoj P. K. (International Journal of Management, IT and Engineering, 2013)
The quality of service provided by real estate agencies to their customers has recently been gained utmost importance in the emerging markets like India. Real estate agencies act as an intermediary for buying and selling of real estate and allied services. This study makes an analysis of the perception of real estate customers regarding the quality of services provided by such agencies with special reference to Kochi (formerly, Cochin) Corporation area in Ernakulam District in Kerala, the southern-most state in the Indian union. Accordingly, the study seeks to identify the drivers of customer satisfaction and hence create better awareness regarding among the real estate agencies regarding these factors; so that these agencies can serve their customers better by improving their service quality. The data collection for this study has been through the use of self-administered questionnaires. A survey of 257 real estate customers has revealed as to what sort of service quality do they really expects from their respective agencies. This study has considered six key factors viz. (i) real estate agent‟s goodwill, (ii) real estate property, (iii) information delivery, (iv) behaviour of agents, (v) punctuality, and (vi) emergency services. The results from statistical analysis indicate that all the above factors lead to customer satisfaction. Among these six factors, the real estate agent‟s goodwill is the most significant factor and emergency services is the least significant factor in deciding the satisfaction level of the customers; though all these factors together decide the overall satisfaction level of the customers. In view of the above, the authors suggest that agencies have to redesign their products and service delivery model, giving due respect to the above factors in their existing business.